INTEGRATING CASE LAW INTO LEGAL EDUCATION: BRIDGING THE GAP BETWEEN THEORY AND PRACTICE - Shoymardonova Mushtariybegim Alisher kizi (Western European Studies, 2025)
This article explores the integration of case law into legal education as a means to bridge the gap between theoretical instruction and real-world legal practice. It highlights how analyzing judicial decisions enhances students’ critical thinking, legal reasoning, and practical application of legal principles. The study emphasizes the value of case-based teaching methods in developing a deeper understanding of law and preparing students for future legal careers. Recommendations are provided on how to effectively incorporate case law into the curriculum to ensure a more dynamic and practice-oriented legal education
Keywords: legal education; case law; judicial decisions; legal reasoning